Corn Wingko Processing Optimization Using Response Surface Methodology - Jariyah Jariyah; Wicaksono L A; Septi N D (International Journal on Food, Agriculture and Natural Resources, 2020)
Wingko is semi-wet food from Indonesia made from grated coconut, glutinous rice flour, sugar and other additives that form a distinctive taste and aroma. Utilization of corn in the form of flour aims to reduce the use of glutinous rice flour as the main composition of wingko because in addition to being an economic commodity, corn contains fiber which is useful for digestion. This study aims to determine the effect of the proportion of corn flour, sticky rice flour and tapioca on the physical and chemical properties of wingko. This study uses the Response Surface Methodology (RSM) method with the experimental design of the Central Composite Design (CCD) using 3 factors of 5 levels, namely the proportion of corn flour (43.18; 50; 60; 70; 76.82) (w / w), flour sticky rice (23,18; 30; 40; 50; 56,82) (w / w), tapioca flour (6,59; 10; 15; 20; 23,41) (w / w) are then processed using Design Expert software 7.1.5. The parameters observed were corn flour including water content, ash, starch, amylose, crude fiber and yield, in glutinous rice flour and tapioca including starch and amylose content, while in wingko products included water content, aw, starch, crude fiber and texture. The results showed that corn flour had a moisture content of 7.12%, ash 0.34%, starch 84.72%, amylose 21.22% of the total ingredients, crude fiber 1.15% and yield of 79.8%. Glutinous rice flour has a starch content of 81.98% and amylose 1.02% of the total ingredients while tapioca flour has a starch content of 78.71% and amylose 20.63% of the total ingredients. The optimum conditions of wingko products were obtained in the proportion of corn flour: sticky rice: tapioca 50:38:20 (w / w) with 23.46% moisture content, aw 0.881, starch content 50.87%, crude fiber 2.78% and texture 0.01194 mm / gs had desirability 0.831.